Methods for Distinguishing Aspen Seedlings from Suckers in the Field - Kreider, Mark R; Mock, Karen E; Yocom, Larissa L (Journal of forestry, 2020)
Abstract Quaking aspen is a common component of postdisturbance landscapes, in part because of its ability to regenerate via asexual suckers. Previously viewed as exceedingly rare in the western United States, sexual seedling establishment is increasingly seen as another important natural regeneration pathway for aspen, because sexual regeneration increases genetic diversity and facilitates long-distance dispersal. However, aspen seedling research is hampered by difficulties in visually distinguishing seedlings from suckers in the field, and few resources exist to guide managers and researchers. We present methods for distinguishing aspen seedlings from aspen suckers, suitable for use in field studies. Using these methods, we achieved 99 percent predictive accuracy in a recently burned area in southern Utah, although accuracy decreased to 90 percent following one summer’s growth, as seedlings and suckers became more similar in appearance. Study Implication: Sexual regeneration may play an important role in aspen’s response to climate change, as it increases genetic diversity and adaptive capacity, and allows aspen populations and their ecological associates to better track changing climate through increased dispersal distances. The methods we present allow managers and researchers to accurately identify aspen seedling populations, which can then be protected and monitored through time to better understand aspen demography and the factors limiting establishment and survival of new clones. Aspen seedling ecology is an area with many knowledge gaps currently, and these methods remove a barrier that has hindered research in the past.